Healing arts therapies and person-centered dementia care - Innes, Anthea; Hatfield, Karen, 1967- (Bradford Dementia Group good practice guides., 2002)
Offering practical advice for arts therapists and health care professionals, this book emphasizes the importance of putting the individual before the illness to provide holistic, person-centred support for people with dementia. The contributors show how music, dance and the visual arts can be used with person-centred care to promote wellbeing.